PERKEMBANGAN TERKINI DALAM DIAGNOSIS DAN PENATALAKSANAAN IRRITABEL BOWEL SYNDROME - Mariadi, I Ketut; Wibawa, I Dewa Nyoman (journal of internal medicine; Vol. 8, No. 3 September 2007, 2012)
Irritable bowel syndrome (IBS) is a common gastrointestinal (GI) motility and sensory disorder that is characterized by abdominal pain/discomfort, bloating and altered bowel habit. The disease accounts for huge costs for both patients and health-care systems and worsens significantly patients’ quality of life. Diagnosis is based on the identification of symptoms according to Manning, Rome I and Rome II criteria and the most recent Rome III criteria and exclusion of alarm indicators. The treatment of IBS is centred on an excellent doctor– patient relationship along with drugs targeting the predominant symptom, especially during exacerbations. This review aim to explain new ctriteria to diagnose IBS and to conduct a systematic evidence-based review of pharmacological therapies currently used, or in clinical development, for the treatment of IBS
Keywords: irritabel bowel syndrome, diagnosis, treatment